Pemetaan partisipatif potensi jasa lanskap kawasan hutan Desa Pattaneteang, Kabupaten Bantaeng - Firnawati Firnawati; Regan Leonardus Kaswanto; Sofyan Sjaf (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Forests are a source of landscape services that are important for the sustainability of ecosystems. The Ministry of Forestry has provided access to village communities to manage forest areas legally, through a village forest scheme with management access rights for 35 years. Participatory mapping is a type of public participation that includes the creation and/or use of spatial information for various purposes. Spatial data allows the identification of relationships between landscape services and landscape characteristics and administrative units. This study aims to identify the potential characteristics and service potentials of the Pattaneteang Village Forest area. The method used in this research is spatial analysis carried out on land use maps based on drone images in Pattaneteang Village and qualitative methods in the form of structured interviews, questionnaires, and focus group discussions. The results showed the quality of landscape services for biodiversity and stored carbon in the Village of Pattaeneteang was in the “very good” level, having a high-value economic role with a total score of 9 in Utilization Village Forest. The total score of the cultural role of the Pattanateang Village Forest is 4 for the Disputed Village Forest and the Utilization Village Forest, which means that it has low cultural value and a value of 5 for the Core Village Forest area which means moderate cultural value.